The Usborne book of farm animals - Everett, Felicity; Lockwood, Rachel; Taylor, Myke (Saffron Hill, London, England : Usborne, 1993)
Simple text and illustrations provide answers to the questions children ask about farm animals, from "What's a baby goat called?" to "How do we get milk from cows?".
Includes index.
4.5
K-3
Keywords: Domestic animals; Domestic animals